Memes de cavaleiros medievais e extrema direita (2016-2023): discussões sobre possibilidades e desafios do ensino de História medieval. - COELHO, Núbia Challine de Oliveira (Universidade Federal do Tocantins, 2024)
The rise of the far right since the second decade of the 21st century has aroused the interest of scholars in various areas of research, such as politics, philosophy, sociology, communication and education. Based on three major structural thematic axes - teaching medieval history, memes of medieval knights and the far right (which in Brazil has made significant progress since 2016) - the aim is to reflect on one of the faces of this rise, which appears in the corridors of a public high school in Palmas/TO: the revival of interest in medieval subjects among young people and the existence of internet memes with the theme of the medieval knight, riddled with inferences of the far right. The fascination with medieval elements is not exclusive to young people in the 21st century, nor is the use of these elements by political groups. However, the world of Web 3.0 (some are already talking about 4.0) has become the environment in which students seek information and through which memes circulate. The aim of this study is therefore to understand the possible impact of the presence of memes of medieval knights associated with far right ideas on the construction of knowledge about the Middle Ages and medieval knights among students at the school in question. Guided by the methodology of action research (Thiollent; Colette, 2014), the empirical research began by analyzing the students' conceptions of the Middle Ages and, in particular, of medieval knights, with the aim of building a comparative picture and collecting information that will form the sources of the research. To this point, workshops and a structured questionnaire were organized using the Google Form. The workshops were designed based on the assumptions of the History class as a workshop (Barca, 2004) and the historical class (Barca, 2012; 2018), as well as the idea of historical literacy (Lee, 2006). Internet memes about medieval knights (selected from those that circulated between 2016 and 2023, with the former president of the Republic, Jair Bolsonaro, as the protagonist) will be disseminated and/or produced by profiles associated with the Brazilian far right) and the data analyzed in the light of the concept of historical consciousness (Rüsen, 2001). As a result of the research, a "Proposal for teaching action" was produced, in the form of an open-access e-book, with suggestions so that teaching professionals can learn about the activities developed and replicate them, if they wish, in their respective realities.